A review of optical gas sensing technology for dissolved gas analysis in transformer oil - Dai, Jialiang; Luo, Bing; Shen, Xiaowen; Han, Wenfei; Cui, Ruyue; Wu, Jintao; Zhang, Haofeng; Xiao, Wei; Zhong, Zheng; Dong, Lei; Wu, Hongpeng (Frontiers in Physics, 2025)
Dissolved gas analysis (DGA) of transformer oil can deeply understand the operation status of oil-immersed transformers, and detect early transformer failures as early as possible, thus achieving the purpose of preventing further damage to the transformer. It is a highly reliable method for identifying early-stage faults in transformers. This paper reviews the commonly used sensing technologies for analyzing dissolved gases in transformer oil, including Raman spectroscopy (RS), fourier transform infrared spectroscopy (FTIR), tunable diode laser absorption spectroscopy (TDLAS) and photoacoustic spectroscopy (PAS). The progress of research on these four gas sensing technologies is reviewed, with a detailed analysis of their respective principles and characteristics. This work provides guidance for the selection of appropriate online gas preliminary sensing technology, which is essential for the assessment of transformer operating conditions to ensure the stable operation of power systems.